What Does South Africa's Pattern of Trade Say About its Labor Markets? - Subramanian, Arvind (IMF Working Papers; Working Paper ;, 2001)
This paper examines the factor intensity of South Africa's trade. The conclusion is that South Africa is revealed though its trade pattern to be capital abundant (relative to labor). Surprisingly, this result holds especially for South Africa's trade with its high income partners, which should presumably have been more capital-rich than South Africa. Moreover, this revealed capital intensity of South African production was not reversed during the 1990s after the dismantling of apartheid. This favoring of capital use, against the background of high and rising under-utilization of the country's labor resources, raises questions about the functioning of South Africa's labor market institutions.